Blimp1/Prdm1 Functions in Opposition to Irf1 to Maintain Neonatal Tolerance during Postnatal Intestinal Maturation. - Arne W Mould; Marc A J Morgan; Andrew C Nelson; Elizabeth K Bikoff; Elizabeth J Robertson (PLoS Genetics)
The neonatal intestine is a very complex and dynamic organ that must rapidly adapt and remodel in response to a barrage of environmental stimuli during the first few postnatal weeks. Recent studies demonstrate that the zinc finger transcriptional repressor Blimp1/Prdm1 plays an essential role governing postnatal reprogramming of intestinal enterocytes during this period. Functional loss results in global changes in gene expression patterns, particularly in genes associated with metabolic function. Here we engineered a knock-in allele expressing an eGFP-tagged fusion protein under control of the endogenous regulatory elements and performed genome wide ChIP-seq analysis to identify direct Blimp1 targets and further elucidate the function of Blimp1 in intestinal development. Comparison with published human and mouse datasets revealed a highly conserved core set of genes including interferon-inducible promoters. Here we show that the interferon-inducible transcriptional activator Irf1 is constitutively expressed throughout fetal and postnatal intestinal epithelium development. ChIP-seq demonstrates closely overlapping Blimp1 and Irf1 peaks at key components of the MHC class I pathway in fetal enterocytes. The onset of MHC class I expression coincides with down-regulated Blimp1 expression during the suckling to weaning transition. Collectively, these experiments strongly suggest that in addition to regulating the enterocyte metabolic switch, Blimp1 functions as a gatekeeper in opposition to Irf1 to prevent premature activation of the MHC class I pathway in villus epithelium to maintain tolerance in the neonatal intestine.